2015
DOI: 10.1177/009164711504300402
|View full text |Cite
|
Sign up to set email alerts
|

Church Support as a Predictor of Children's Spirituality and Prosocial Behavior

Abstract: Church affiliation has been associated with many developmental benefits for children and adolescents, including higher levels of prosocial behavior; however, research has only minimally explored the mechanisms mediating these relationships. The current study examines the extent to which social support at church (i.e., church support) predicts children's prosocial behavior independent of family religious practices and, subsequently, the extent to which the relationships between family religious practices, churc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
0
14
0
2
Order By: Relevance
“…Crosby et al (2015) defined social support as a feeling of belonging, being cared for, and loved. Crosby and Smith (2015) found church support significantly predicted prosocial behavior and spirituality when controlling for family religious practices. Children who perceived their church to be friendly and loving were more likely to believe God was close and responsive.…”
Section: Independent Variablesmentioning
confidence: 91%
See 1 more Smart Citation
“…Crosby et al (2015) defined social support as a feeling of belonging, being cared for, and loved. Crosby and Smith (2015) found church support significantly predicted prosocial behavior and spirituality when controlling for family religious practices. Children who perceived their church to be friendly and loving were more likely to believe God was close and responsive.…”
Section: Independent Variablesmentioning
confidence: 91%
“…Studies using SDT as a framework for investigating parental and church support for identified religiosity in children and adolescents have focused on autonomy and relatedness (Assor et al, 2005; Flor & Knapp, 2001). Research identifies positive connections between children’s religiosity and autonomy support in church (Beste, 2012; Ridgely, 2006) and relatedness in church (Crosby, Smith, & Frederick, 2015; Crosby & Smith, 2015). In order to ensure strong empirical support and narrow the scope of the study the researcher designed this current study to explore the needs of autonomy and relatedness in a church context.…”
Section: Independent Variablesmentioning
confidence: 99%
“…For example, nurturing and supportive relationships within the church community may engender a corresponding concept of God, similar to the way parents’ behaviors do in early childhood (Dickie et al, ; Krause & Ellison, ). The resulting perception of God as loving and responsive is a significant facet of religious support (Pargament, ) which has been associated with a number of positive youth outcomes, including life satisfaction, prosocial behavior, and religious coping (Bjorck, Kim, Braese, & Gililland, ; Crosby & Smith, ; Van Dyke, Glenwick, Cecero, & Kim, ).…”
Section: The Present Studymentioning
confidence: 99%
“…Parent support was measured using the six‐item parent subscale of the self‐report Social Support Scale for Children (Harter, ). Family religious practices was measured using a three‐item parent‐report measure adapted by Crosby and Smith () from existing inventories of adult and family religious practices. School support was measured using the five‐item peer support subscale and the four‐item teacher support subscale of the self‐report Psychological Sense of School Membership survey (Goodenow, ; Ye & Wallace, ).…”
Section: Instrument Validationmentioning
confidence: 99%
“…Such evolution consists of overcoming the initial structural nature to build up another one qualitatively different [2][3][4][5]. Much research and philosophical reflection has been done on religiosity and motivation toward moral and pro-social behaviour [6][7][8][9][10][11][12][13][14][15]. Teachers are the most imperative tool in refining schools and contributing to student accomplishment [16,17].…”
Section: Introductionmentioning
confidence: 99%